A consecutive case series of defects reconstructed using NovoSorbⓇ Biodegradable Temporising Matrix: Initial experience and early results. Issue 10 (October 2020) - Solanki, Nicholas S.; York, Blair; Gao, Yang; Baker, Paul; Wong She, Richard B
Abstract: Background: NovoSorb Ⓡ Biodegradable Temporising Matrix (BTM) is a synthetic dermal template recently approved for treatment of full thickness defects of the skin. It requires a two-stage reconstruction where it is initially placed into a defect to generate a neodermis, which is later covered by a split skin graft. It has previously been described for the treatment of acute full thickness burn injury, necrotising fasciitis and free flap donor site reconstruction. Methods: A consecutive case series review of patients treated with BTM at Middlemore Hospital was performed. Patient demographics, defect aetiology, indications for dermal matrix use, surgical details, and complications were recorded using information gathered from the medical records. Results: This case series included 25 patients with a range of defects resulting from acute full thickness burn injury, burn scar revision, necrotising soft-tissue infection, tumour excision and traumatic loss. In these patients, 72% of wounds were identified as complex defects with exposed bone or tendon. Complications encountered included infection, non-adherence and incomplete vascularisation. Conclusion: BTM provided a good reconstructive option for a wide range of defects, many of which were not amenable to immediate skin grafting. Once vascularised and ready for the second stage, it developed a red-pink colour and demonstrated capillary refill. Similar to other dermal matrices, infection was a commonly encountered problem. However, BTM proved more tolerant to this and was able to be salvaged in most cases, allowing the second stage to proceed as normal.